High SERS Sensitivity Enabled by Synergistically Enhanced Photoinduced Charge Transfer in Amorphous Nonstoichiometric Semiconducting Films. Issue 19 (23rd August 2019) - Fan, Xingce; Li, Mingze; Hao, Qi; Zhu, Minshen; Hou, Xiangyu; Huang, Hao; Ma, Libo; Schmidt, Oliver G.; Qiu, Teng
Abstract: Semiconducting surface‐enhanced Raman scattering (SERS) materials have attracted tremendous attention for their good signal uniformity, chemical stability, and biocompatibility. Here, a new concept to design high sensitivity semiconducting SERS substrates through integration of both amorphous and nonstoichiometric features of WO3− x thin films is presented. The integration of these two features provides narrower bandgap, additional defect levels within the bandgap, stronger exciton resonance, and higher electronic density of states near the Fermi level. These characteristics lead to a synergy to promote the photoinduced charge transfer resonance between analytes and substrate by offering efficient routes of charge escaping and transferring as well as strong vibronic coupling, thus realizing high SERS activity on amorphous nonstoichiometric WO3− x films. Abstract : The integration of amorphous and nonstoichiometric features of semiconducting surface‐enhanced Raman scattering (SERS) materials can lead to synergistically enhanced photoinduced charge transfer resonance between substrate and analytes by offering efficient routes of charge escaping and transferring as well as strong vibronic coupling, thereby enabling dramatically promoted SERS performance.